The Renaissance : a very short introduction - Brotton, Jerry; Brotton, Jerry (Oxford [England] ; New York : Oxford University Press, 2005)
In this wide-ranging exploration of the Renaissance, Jerry Brotton shows the period as a time of unprecedented intellectual excitement, cultural experimentation, and interaction on a global scale, alongside a darker side of religion, intolerance, slavery, and massive inequality of wealth and status.-publisher description
A global Renaissance -- The humanist script -- Church and state -- Brave new worlds -- Science and philosophy -- Rewriting the Renaissance
Revised edition of: The Renaissance bazaar. 2002
Includes bibliographical references (pages 133-135) and index
Keywords: Renaissance; East and West; Europe -- History -- 1492-1648